Academic support through tutoring, guided learning, and learning diaries in the context of the COVID-19 pandemic: an experimental model for master’s students - Dumitru, Cristina; Stan, Maria Magdalena; Dumitru, Georgiana (Frontiers in Education, 2024)
Introduction Engaging students in co-planning their learning paths, peer cooperation, tutoring, and network building in an inclusive and project-based environment has been associated with higher academic and professional success. However, university teachers face challenges in offering guidance and academic supervision to optimize student learning, particularly in the context of online learning. This study aimed to investigate the effectiveness of adapting collaborative learning environments, peer tutoring, and academic supervision in the online learning space. Methods An experimental design methodology was employed to investigate the impact of collaborative learning environments, peer tutoring, and academic supervision on student engagement, interest, and dedication to learning. Results The findings showed direct positive effects on the level of engagement (VI; M = 23.18, SD = 5), higher interest and dedication to the learning process (DE: M = 26.93, SD = 3.21), and better concentration and enthusiasm while studying (AB, M = 24.83, SD = 8.52). Discussion The results suggest that adapting to online learning by providing collaborative learning environments, peer tutoring, and academic supervision can enhance student engagement and motivation. Further research is needed to explore the long-term effects and scalability of these interventions in diverse educational contexts.